Primary renal well-differentiated neuroendocrine tumour (carcinoid): next-generation sequencing study of 11 cases - Pivovarcikova, Kristyna; Agaimy, Abbas; Martinek, Petr; Alaghehbandan, Reza; Perez-Montiel, Delia; Alvarado-Cabrero, Isabel; Rogala, Joanna; Kuroda, Naoto; Rychly, Boris; Gasparov, Slavko; Michalova, Kvetoslava; Michal, Michal; et al. (Histopathology, 2019)
AIMS: Primary renal well-differentiated neuroendocrine tumour (NET) (hereafter referred to as renal NET) is rare, with ~100 cases having been reported in the literature. There are also limited data on the molecular-genetic background of primary renal NETs. METHODS AND RESULTS: We analysed 11 renal NETs by using next-generation sequencing (NGS) to identify characteristic genetic aberrations. All tumours were positive for synaptophysin, and also expressed insulinoma-associated protein 1 (10/11), chromogranin-A (8/11), and CD56 (3/11). Cytoplasmic positivity of CD99 was present in eight of 11 cases, and strong nuclear expression of α-thalassaemia/mental retardation syndrome X-linked (ATRX) was retained in all 11 cases. Molecular-genetic analysis of aberration of VHL gave negative results in all cases. Loss of heterozygosity on chromosome 3p21 was found in three of nine analysable cases. NGS was successful in nine cases, showing a total of 56 variants being left after the updated filtering process, representing an average of five variants per sample. All analysable cases were negative for ATRX and DAXX (death-domain associated protein X) mutations. The most frequently mutated genes were CDH1 and TET2, with three mutations in two cases. Mutations in AKT3, ROS1, PIK3R2, BCR and MYC were found in two cases. The remaining 41 genes were found to be mutated only in individual cases. In four cases, the mutations affected a subset of genes related to angiogenesis. CONCLUSIONS: Overall, the mutation profile of primary renal NETs is variable, and none of the studied genes or affected pathways seems to be specific for renal NET.
Keywords: senioři; primary; DNA-Binding Proteins; Dioxygenases; Cell Differentiation; kadheriny; senioři nad 80 let; lidé; imunohistochemie; Middle Aged; Neuroendocrine Tumors; kidney; mužské pohlaví; next-generation sequencing; Proto-Oncogene Proteins; mutace; carcinoid; Adult; Loss of Heterozygosity; well-differentiated neuroendocrine tumour; Kidney Neoplasms; Biomarkers, Tumor; ztráta heterozygozity; Aged, 80 and over; Immunohistochemistry; karcinoid; dioxygenasy; ženské pohlaví; nádorové biomarkery; Mutation; Humans; High-Throughput Nucleotide Sequencing; Cadherins; Antigens, CD; lidé středního věku; protoonkogenní proteiny; vysoce účinné nukleotidové sekvenování; DNA vazebné proteiny; buněčná diferenciace; dospělí; neuroendokrinní nádory; Female; Aged; CD antigeny; Carcinoid Tumor; nádory ledvin; Male